Short pulses of epiretinal prostheses evoke network-mediated responses in retinal ganglion cells by stimulating presynaptic neurons - Roh, Hyeonhee; Otgondemberel, Yanjinsuren; Im, Maesoon (Institute of Physics Publishing, 2022)
Objective. Microelectronic retinal implant aims to restore functional vision with electric stimulation. Short pulses are generally known to directly activate retinal ganglion cells (RGCs) with a notion of one or two spike(s) per pulse. In the present work, we systematically explore network-mediated responses that arise from various short pulses in both normal and degenerate retinas. Approach. Cell-attached patch clamping was used to record spiking responses of RGCs in wild-type (C57BL/6J) and retinal degeneration (rd10) mice. Alpha RGCs of the mouse retinas were targeted by their large soma sizes and classified by their responses to spot flashes. Then, RGCs were electrically stimulated by various conditions such as duration (100-460 mu s), count (1-10), amplitude (100-400 mu A), and repeating frequency (10-40 Hz) of short pulses. Also, their responses were compared with each own response to a single 4 ms long pulse which is known to evoke strong indirect responses. Main results. Short pulses evoked strong network-mediated responses not only in both ON and OFF types of RGCs in the healthy retinas but also in RGCs of the severely degenerate retina. However, the spike timing consistency across repeats not decreased significantly in the rd10 RGCs compared to the healthy ON and OFF RGCs. Network-mediated responses of ON RGCs were highly dependent on the current amplitude of stimuli but much less on the pulse count and the repetition frequency. In contrast, responses of OFF RGCs were more influenced by the number of stimuli than the current amplitude. Significance. Our results demonstrate that short pulses also elicit indirect responses by activating presynaptic neurons. In the case of the commercial retinal prostheses using repeating short pulses, there is a possibility that the performance of clinical devices is highly related to the preserved retinal circuits. Therefore, examination of surviving retinal neurons in patients would be necessary to improve the efficacy of retinal prostheses.